Implementasi Monitoring Perkembangan Proyek Konstruksi Pada Perum Perumnas Jakarta Berbasis Web - Yoseph Tajul Arifin; Instianti Elyana; Rahmat Hidayat; Titik Misriati; Norma Yunita (Paradigma, 2018)
One factor of success in a housing construction project is the monitoring of each division that is interrelated and connected with each other. It would be very inefficient if from each party there was no clear and uncontrolled communication. As with the Jakarta Housing Corporation, currently monitoring the project has not been well integrated. Where information that is intertwined with regional offices is still limited to communication information by telephone, as well as data that is used using documents or archives that can sometimes be lost or forgotten in the storage. Of course this will slow down the project development process, because it is constrained by each of the relevant parties, plus the report must be presented or needed at any time by the director. For this reason, a system that can support the monitoring process is needed so that data can be stored properly and the control of the progress of each project is monitored from the center. One of them is the creation of a web-based system application, with this system all can be done in real time.